(untitled) (Research, Society and Development, 2019)
The objective of this study is to analyze how the Adventure Body Practices (PCA) were developed in the school in the last 10 years; whose descriptors - sports, adventure, corporal practices, content, physical education, nature, environment, allowed to find 122 studies in 4 databases: Scielo; Google Scholar, Redalyc and Lilacs. Five studies were selected according to the inclusion and exclusion criteria. It is possible to observe didactic-pedagogical practices, when contemplating the dimensions of the contents, narrowing the relation between the human being and the nature. However, we conclude that the potential of PCA for cognomotor development was not addressed in the studies, in their dimensions of interconnected cognitive and motor functions, making us infer that the current paradigm is not yet embodied cognition, where body and mind are inextricably together. It is up to teachers, education secretariats and higher education institutions to foster specific training both in undergraduate and postgraduate courses.